Putting Self-Management in the Context of Community-Dwelling American Indians Living With Type 2 Diabetes. Issue 1 (February 2020) - Jones, Jacqueline; Goins, R. Turner; Schure, Mark; Winchester, Blythe; Bradley, Vickie
Purpose: The purpose of this qualitative descriptive study was to examine the National Standards for Diabetes Self-Management Education and Support (DSMES) defined diabetes self-care behaviors (healthy eating, being active, taking medication, monitoring, problem solving, reducing risk, and healthy coping) in the context of older community-dwelling American Indians (AIs). Methods: Secondary theme analysis of transcribed semistructured qualitative interview data from 28 participants in the Native Elder Care Study aged >60 years identified factors that influence the DSMES self-care behaviors in the context of community-dwelling AIs. Results: Four themes that characterized barriers, facilitators, and opportunities for DSMES to support self-care behaviors included community food security, care partners in self-care, community opportunities for diabetes support, and blending of both health worlds. Conclusion: Tribal communities have contemporary strengths and cultural traditions that can be activated to enhance diabetes self-management education and support. Diabetes educators can work in tandem with community health representatives to strengthen the social and community support within which individual AIs with type 2 diabetes mellitus live. Community-based participatory research with AI caregivers, dyads, families, youth, and Indian Health Service clinicians may help to improve tribal food policy and school health initiatives, as well as develop intergenerational interventions for modeling effective diabetes self-management.